2019
DOI: 10.33225/jbse/19.18.955
|View full text |Cite
|
Sign up to set email alerts
|

Development of Estonian Upper Secondary School Students’ Biological Conceptual Understanding and Competences

Abstract: The main aim of this research was to measure 10 th and 12 th grade students' biological conceptual understanding and competences through their upper secondary school studies. Data collection started at the beginning of the upper secondary school biology studies in the 10 th grade. The same students participated in this research when they were in the 12 th grade. A validated instrument of covering four competences: biological conceptual understanding, problem-solving, critical thinking and divergent thinking wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Thereby, engaging students in SSI and science practices not only develops scientific/chemical literacy but also links societal issues with the nature of science and 21 st century skills (Romine et al, 2016;Zeidler, 2015). Therefore, SSI-based instruction requires students to go beyond conceptual understanding (Feierabend & Eilks, 2011;Ke et al, 2020) and improves their critical thinking skills within an informed way or informal reasoning (Semilarski et al, 2019;Zeidler & Nichols, 2009). Although SSI-based instruction, as an interdisciplinary and multidimensional approach, embraces several subjects (i.e., biology, chemistry, ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ physics, earth sciences, environmental sciences and so forth), it generally employs a core subject (e.g., chemistry) to frame features and outcomes of student learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, engaging students in SSI and science practices not only develops scientific/chemical literacy but also links societal issues with the nature of science and 21 st century skills (Romine et al, 2016;Zeidler, 2015). Therefore, SSI-based instruction requires students to go beyond conceptual understanding (Feierabend & Eilks, 2011;Ke et al, 2020) and improves their critical thinking skills within an informed way or informal reasoning (Semilarski et al, 2019;Zeidler & Nichols, 2009). Although SSI-based instruction, as an interdisciplinary and multidimensional approach, embraces several subjects (i.e., biology, chemistry, ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ physics, earth sciences, environmental sciences and so forth), it generally employs a core subject (e.g., chemistry) to frame features and outcomes of student learning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chemistry-focused SSI directly covers conceptual understanding of chemistry and chemical literacy for all students by linking school chemistry with daily life (i.e., Koçak Altundağ, 2018;Ültay & Çalik, 2012;Versprille et al, 2017) and any scientific, technological and environmental development (Gilbert & Treagust, 2009;Mozeika & Bilbokaite, 2010;Zahara & Atun, 2018). Because chemistry plays a milestone in addressing chemistry-focused SSI and finding alternative ways or solutions (Bertozzi et al, 2016;Seery, 2015), students are able to explore chemical problems using conceptual and procedural connections and judge social significance of chemistry on the community or daily life. For example, Eilks et al (2018) used some chemistry-focused SSI (e.g., musk fragrances in shower gels, low-fat and low-carb diets, doping in professional and leisure sports, bioplastics, Stevia controversy, natural cosmetics, and tattooing) to inform students about responsible citizenship and scientific/chemical literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of instruments were used for data collection—(a) a questionnaire (experimental and control group) and (b) interviews (experimental group). Questionnaire A pre- and post-questionnaire (Semilarski et al, 2019a ; Soobard et al, 2018 ) was used for determining students’ perceived self-efficacy, related to the core ideas. This was administered to obtain an overview of the effectiveness of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, students’ perceived self-efficacy tends to be higher towards DCIs related to Life Science and Earth Science and lower towards DCIs related to Chemistry and Physics, where the knowledge tends to be more abstract (Cheung, 2015 ; Jamil & Mahmud, 2019 ; Semilarski et al, 2019a ; Soobard et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 95%
“…The achievement enhancement in every level of higher education is continually encouraged, but various problems with low achievement were still found, especially in biology education students (Gao, 2014;Purnawan, 2018;Semilarski, Laius & Rannikmäe, 2019). The preliminary researches result at STKIP Persada Khatulistiwa also showed that the average biology students' achievement in the zoology lecture was as much as 60.98 and still in enough category.…”
Section: Introductionmentioning
confidence: 99%